Controversies in zakat: an effective method of resolution - Tahir, Ibrahim Nuhu; Oziev, Gapur (IIUM Press, International Islamic University Malaysia, 2018)
Perhaps zakāt is the only pillar of Islam which has been so widely disputed by scholars with regard to its rulings, application and above all necessity of modification. The Muslim Ummah has witnessed widespread misconceptions about some rulings and application of zakāt mainly due to usage of weak and unreliable aḥādīth. It must be noted that zakāt rulings are fixed by Sharīʽah and cannot be altered or modified due to the change of time and circumstance. Therefore, any discussion, argument, suggestion and criticism can only be based on authentic sources of Sharīʽah. It is imperative that the person attempting to face the challenges or to resolve controversies on zakāt has to be well versed in the major Sciences of Sharīʽah. These sciences are Qur’ān, Ḥadīth, Islamic Jurisprudence, Arabic language as well as their principles or sciences. The paper focuses on the following aspects: the critical areas of Ijtihād on controversial issues and how they could be resolved by using the method of combining the nusus to produce a reasonable conclusion. The paper has adopted descriptive, deductive and historical methods of analysis.